Analisis Produktivitas Tenaga Kerja Wanita Pada Industri Rambut Palsu - Aisyah, Fiki Dwi; Oktavilia, Shanty (Universitas Negeri Semarang, 2020)
The wig industry in Purbalingga has excellent prospects in supporting the pace of the regional economy and has great potential to expand job opportunities so as to reduce the number of unemployed. The purpose of this study was to analyze the effect of wages, length of study, work experience on the productivity of female workers in the wig industry in Purbalingga Regency. The sample used is 100 respondents of female workers who work in the medium-large industry and the small wig industry in Purbalingga Regency. The variables of this research are wages (X1), length of study (X2), work experience (X3), industry category (dummy variable), and productivity (Y). Data collection methods used are literature review, observation, questionnaires, and interviews. The data were analyzed using a quantitative descriptive analysis method and multiple linear regression using the help of Eviews. The results showed that the wage variables, length of study, work experience have a positive and significant effect on the productivity of women workers in the wig industry in Purbalingga Regency. Industri rambut palsu di Kabupaten Purbalingga memiliki prospek yang besar dalam menopang laju perekonomian dan membuka kesempatan kerja sehingga dapat mengurangi angka pengangguran. Tujuan penelitian ini yaitu untuk menganalisis pengaruh upah, lama menempuh pendidikan, pengalaman kerja terhadap produktivitas tenaga kerja wanita pada industri rambut palsu di Kabupaten Purbalingga. Sampel yang digunakan berjumlah 100 responden terdiri dari tenaga kerja wanita yang bekerja pada industri menengah besar dan pada industri kecil rambut palsu di Kabupaten Purbalingga. Variabel penelitian ini adalah upah (X1), lama menempuh pendidikan (X2), pengalaman kerja (X3), kategori industri (variabel dummy) dan produktivitas (Y). Metode pengumpulan data yang digunakan adalah metode kajian pustaka, observasi, kuesioner, dan wawancara. Data dianalisis menggunakan metode analisis deskripstif kuantitatif dan uji regresi linier berganda dengan bantuan Eviews. Hasil penelitian menunjukan upah, lama menempuh pendidikan, pengalaman kerja berpengaruh positif dan signifikan terhadap produktivitas tenaga kerja wanita pada industri rambut palsu di Kabupaten Purbalingga.